Glycemic Response And Cumulative Glucose After High Intensity Aerobic And Anaerobic Exercise In Athletes And Non-Athletes - Shatha Hazim Gorgees Hana, (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Aim of current study Know response of blood sugar level and accumulative sugar after high intense aerobic and anaerobic exercises for practioners and non practioners  -know differences between pre-post tests in blood sugar level and accumulative sugar after high intense aerobic and abaerobic exercises for practioners and non practioners Researcher hypothesized existence of morally significant differences in blood sugar level and accumulative sugar after high intense aerobic and abaerobic exercises for practioners and non practioners, existence of morally significant differences between pre-post tests in blood sugar level and accumulative sugar after high intense aerobic and abaerobic exercises for practioners and non practioners. Sample were (17) students who are enrolled in athletic activities and a similar number of non practioners who spend most time sitting from departments of geography and history both samples were chosen intentionally. Researcher used the following statistical tools means, standard deviation, t-test for irrelated samples , variance factor. Conclusions high intensity aerobic exercise (Bruce) and anaerobic one cause a moral variance in each of the following variables : number of breathing , heart beats , shrinking blood pressure, recess blood pressure, blood sugar. Both exercises didn't make moral variance in accumulative blood sugar.